Ukraine : First Review Under the Extended Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Ukraine's First Review Under the Extended Arrangement. The authorities have made a strong start in implementing the program. All performance criteria (PCs) for end-March 2015 and, based on preliminary information, all PCs for end-June were met. Eight benchmarks were completed, albeit four of them with a delay and two were converted into prior actions for this review. Discussions with creditors have made progress toward a debt operation that would restore fiscal sustainability. In view of the authorities' performance under the program, their policy commitments for the period ahead, and progress toward a debt operation in line with its stated objectives, the IMF staff recommends the completion of the first review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet